Can social assistance reduce violent conflict and civil unrest? Evidence from a large-scale public works program in Ethiopia - Hirvonen, Kalle; Machado, Elia; Simons, Andrew M. (International Food Policy Research Institute, 2024)
Violent conflict and political instability are escalating worldwide, with Africa experiencing some of the most severe challenges. The region, home to 60% of the world’s poor (World Bank 2023), saw statebased armed conflict events nearly triple between 2007 and 2023 (Rustad 2024), while protests more than quadrupled from 2007 to 2019 (OECD 2021). Over this period, poverty reduction in Africa has been particularly sluggish in fragile and conflict-affected areas (Beegle et al. 2018a), likely due to the substantial economic losses associated with violent conflict and civil unrest.